A survey of the history and cultural practices of some ethnic groups of North central Nigeria in pre-christianity era (2012)
Any attempt to embark on writing the history of peoples and their cultural norms and practices is designed with a view to make readers have deeper understanding of the peoples, culture and politics of a particular geographical entity. Nigeria as heterogeneous state has over 250 ethnic groups with powerful ones exercising undue domination over the weaker ethnic groups. Three significant factors necessitated the need to embark on this project. The first is the monumental and historical misplacement of Kogi and Kwara States in the North Central Nigeria, a product of colonialism and military rule in Nigeria. This argument is premised on the presence of a large population of the Yoruba in the two states which used to be part of Old Oyo kingdom. Secondly, most scholars seem not to have taken adequate cognizance of the Yoruba stock in the two states under review. Attention had been centred on the Yoruba people and culture in south western Nigeria. Therefore, there is the need to fill the gap by documenting the history and culture of these peoples. Furthermore, the paper articulates the implication of cultural contact with foreign religions. To an extent, moral laxity in the country is traceable to foreign influence on Nigerian peoples who abandoned their cultural heritage and fail to teach them to the succeeding generation. The paper concludes by advocating a new orientation towards inculcating the good morals and values into the younger generation.